Was Croatian Literary Modernism Anti-Catholic? One Conceptual Aspect of the Dispute Between “the Old” and “the Young” in Croatian Literature at the End of the 19th and the Beginning of the 20th Century - Lončarević, Vladimir (Poznańskie Studia Slawistyczne, 2016)
An interesting conceptual dispute, usually called a confrontation between “the old” and “the young”, developed at the end of the 19th and the beginning of the 20th century. Although by its name defined as a “clash of generations”, the dispute was basically rooted in differences between two groups of writers concerning their attitudes toward arts: of traditionalists, whose starting point was the principle of the unity of truth, beauty and good, and of modernists, who relied on aestheticism and concept of l’art pour l’art’. “The young”, while upholding individualism, particularly used to stress their anti-Catholicism. The author checks whether at their root there was anti-Catholicism. He comes to the conclusion that Croatian Moderna was not an organised anti-Christian or anti-Chatolic movement, even though it isn’t doubtful that anticlericalism of “the young”, to a large degree, assumed contours of antagonism towards public expression of Catholicism in culture, harbingering at the same time secularist conceptual processes that were expressed later in the political field and all the other fields of social life.